Mehrdimensionale Bildung im Kontext Kommunaler Bildungslandschaften Bestandsaufnahme und Perspektiven - Berse, Christoph (Erziehungswissenschaft, 2009)
The book reflects the productive approaches of multidimensional educational concepts in the redesign of municipal educational landscapes against the background of expanded educational concepts and the current educational discourse in Germany. In addition, the educational policy orientation of child and youth welfare is discussed as an ambivalent guiding norm and the various approaches to cooperation between youth welfare and schools and full-time education are presented.